2018
DOI: 10.21608/ejhc.2018.19869
|View full text |Cite
|
Sign up to set email alerts
|

Training of Nurses on Rehabilitation of Patients with Spinal Cord Injuries

Abstract: Nursing activities and caring should be superior in spinal cord injury rehabilitation, in order to teach care to the family and the patient, nurses should have enhanced knowledge and skills about spinal cord injury and prevention of complications. The aim of the study was to evaluate the effect of a training program for nurses on rehabilitation of clients with spinal cord injuries. Design: A quasi-experimental study design. Setting: The study was conducted at the Physical Medicine and Rehabilitation and Rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…As regard to attending previous training programs, the present results showed that the most of the nurses had no previous training courses; this may be due to shortage of nursing staff and work load at ICU. This results is similar to Abd-Elhameed and Sayed (21) in their study revealed that more than half of the studied nurses did not receive any previous training regarding rehabilitation, while this result is dissimilar to Eid et al (20) who revealed that about three quarters of studied nurses had training course about trauma patients.…”
Section: Discussionsupporting
confidence: 82%
“…As regard to attending previous training programs, the present results showed that the most of the nurses had no previous training courses; this may be due to shortage of nursing staff and work load at ICU. This results is similar to Abd-Elhameed and Sayed (21) in their study revealed that more than half of the studied nurses did not receive any previous training regarding rehabilitation, while this result is dissimilar to Eid et al (20) who revealed that about three quarters of studied nurses had training course about trauma patients.…”
Section: Discussionsupporting
confidence: 82%